2018
DOI: 10.15694/mep.2018.0000107.1
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for self-directed learning among basic science and premedical students at a Caribbean medical school

Abstract: Introduction: Self-directed learning (SDL) skills are becoming increasingly important in modern medical education. Readiness for SDL among medical students can be measured using the scale of Hendry and Ginns. The present study was conducted at an offshore Caribbean medical school to measure SDL readiness among premedical and basic science students. Methods:The study was conducted during March 2018 using the instrument mentioned previously. The survey was administered online. Gender and semester of study were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The results of many studies, using various SDLRS instruments, indicate that medical students are ready to engage in SDL; 26 , 34 , 35 , 47 49 however, without qualitative data, the SDLRS scores alone may not provide a full understanding of their SDL abilities. 37 Qualitative analysis of student perceptions is essential to provide insight into the impact of the medical school experience on the development of SDL.…”
Section: Discussionmentioning
confidence: 99%
“…The results of many studies, using various SDLRS instruments, indicate that medical students are ready to engage in SDL; 26 , 34 , 35 , 47 49 however, without qualitative data, the SDLRS scores alone may not provide a full understanding of their SDL abilities. 37 Qualitative analysis of student perceptions is essential to provide insight into the impact of the medical school experience on the development of SDL.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed no significant difference between male and female students in their approach to SDL, which is in line with literature. 1,12,13 However, studies from Italy and China have reported contradictory results, too. 10,14 Further assessment is therefore required before a meaningful conclusion can be drawn about this relationship.…”
Section: Discussionmentioning
confidence: 99%